ANTI-STRESS ACTION OF SEVERAL ORALLY-GIVEN β-GLUCANS - Vetvicka, Vaclav; Vancikova, Zuzana (Biomedical papers, 2010)
Background: β-Glucans are well-established immunomodulators. Recently, glucans have been found to influence stress-related immunosuppression.Aim: The aim of this study was to compare the effects of four different types of β-glucans on immune reactions suppressed by cold- or restrain-induced stress.Methods: Mice were subjected to restraint and cold stress for various time intervals. The ability of individual glucans to overcome stress-related changes was evaluated after 14 days of feeding.Results: First, we showed that cold stress caused 38% decrease in phagocytic activity. While all glucans showed some ability to inhibit stress-related inhibition, only glucan #300 was able to return the phagocytosis to a normal level. In the control group, feeding with glucans did not alter the level of corticosterone. On the other hand, both types of stress resulted in a significant increase in corticosterone which was blocked to some extent by feeding with glucan. Both types of stress reduced IL-6 secretion but only glucan #300 managed to keep IL-6 secretion above control levels. The same results were obtained in the case of IL-12.Conclusion: From our data, we can conclude that, even when all orally-administered glucans helped to restore the stress-related decrease in immune reaction, the level of activity varied widely among individual glucans. In addition, the results suggest that glucans might work via inhibition of corticosterone levels and/or stimulation of cytokine production.
Keywords: Keywords: Glucan/Stress/Immunomodulator/Cytokines